A comparative study of elective nodal irradiation and involved field irradiation in elderly patients with advanced esophageal cancer - Dai, Yuanfei; Huang, Di; Zhao, Wei; Wei, Jie (Frontiers in Oncology, 2023)
Objective This comparative study aimed to explore the feasibility of involved field irradiation (IFI) in the radiotherapy of elderly patients with advanced esophageal cancer, compared with elective nodal irradiation (ENI). Methods A total of 245 elderly patients (age ≥70 years) with advanced esophageal cancer, who received radiotherapy in our department from January 2014 to December 2020, were divided into the ENI group (n=111) and the IFI group (n=134). Clinical efficacy, toxicities, survival rates, treatment failures, and multifactorial survival analyses were conducted for both groups. Results The ENI group and the IFI group showed no significant differences in terms of short-term efficacy (91.9% vs 91.0%, P=0.814), 1-year overall survival (OS) (81.1% vs 74.6%, P=0.228), 2-year OS (22.5% vs 25.4%, P= 0.603), 1-year progression-free survival (PFS) (56.8% vs 51.5%, P= 0.198), 2-year PFS (8.1% vs 9.0%, P=0.814), regional failures (38.7% vs 31.3%, P=0.226), and distant metastasis (21.6% vs 14.9%, P=0.174). The median overall survival (OS) was 19 months in the ENI group and 18 months in the IFI group (Log-rankχ2 = 0.012, P=0.913). The median progression-free survival (PFS) was 13 months in the ENI group and 11 months in the IFI group (Log-rankχ2 = 1.834, P=0.176). There were no significant statistical differences in both OS and PFS (P>0.05). The incidence of grade ≥3 radiation pneumonia and grade ≥3 radiation esophagitis in the IFI group was 8.2% and 11.2%, respectively, which were significantly lower than those in the ENI group (17.1%, P=0.034; 21.6%, P=0.026). Univariate analysis revealed that age, gender, T stage, N stage, and synchronous chemotherapy were factors affecting prognosis. Multivariate analysis showed that age, gender, T stage, and synchronous chemotherapy were independent prognostic factors, with hazard ratios of 1.227, 1.466, 2.441, and 2.714, and P values of <0.001, 0.006, <0.001, and<0.001, respectively. Conclusion IFI is a suitable choice for elderly patients with advanced esophageal cancer, as it yields similar efficacy to ENI while reducing toxicities. Age, gender, T stage, and synchronous chemotherapy are independent prognostic factors for elderly patients with esophageal cancer.